Analisis Kemampuan Berpikir Kreatif Siswa Kelas X3 SMA Negeri 1 Watang Pulu dalam Pembelajaran Berbasis Masalah pada Materi Pokok Reaksi Redoks - Maya Maya; Army Auliah; Alimin Alimin (ChemEdu, 2020)
The aim of this deskriptif research is to determine how Student’s Creative Thinking Skill by Using Problem Based Learning to Students of Class X3 SMAN 1 Watang Pulu in Material of Oxidation Reduction Reactions. This research is descriptive research that aims to describe the students ability of creative thinking (fluency, flexibility, originality, and elaboration) in problem based learning, of redoks reaction as main topic. The research subjects are all students of Class X3 SMAN 1 Watang Pulu that consist of 32 students. The data was collected by observation sheet and giving 7 validated items of learning research test. The data was analyzed by descriptive statistic. The result of analysis showed that the average value of creative thinking ability for fluency is 75,05% (good category), flexibility is 73,44% (good category), originality is 72,66% (good category), and elaboration is 75,78% (good category). The average value of four times meeting is 62,79% (good category). The student activity that good category same with the study result. This research showed that student ability of creative thinking in problem based learning on redoks reaction main topic was classified as good category.